Review of CCSP draft synthesis and assessment product 5.3 decison- support experiments and evaluations using seasonal to interannual forecasts and observational data (National Academies Press, 2008)
This study offered an independent peer review for a synthetic document being produced for the CCSP. It found the draft document to be in a fairly early stage of development and noted several issues needing attention in the revision. The draft was inconsistent across sections with respect to whether or not it accepted two assumptions: that more skillful forecasts necessarily have greater value, and that the most useful form of information is a projected future value of an outcome parameter with an uncertainty distribution. Available scientific evidence gives reason to question these assumptions, and the draft did not discuss the evidence. Among other issues needing attention, the review called for the revised draft to do more to substantiate its claims of the potential benefits of knowledge-action networks and to give more careful consideration to the appropriate balance of roles between governmental and private efforts.